2009
DOI: 10.1124/jpet.109.158717
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of Chronic Fluoxetine Treatment on Neuroplasticity and Pharmacokinetics in Mice

Abstract: Neurogenesis is a mechanism through which antidepressants may produce therapeutic effects. There is a dearth of information regarding the effects of antidepressants on neurogenesis and neurotrophin mobilization in females. This study examined sex differences in the alteration of cell proliferation and survival in multiple regions of the brain. Additional experiments examined brain-derived neurotrophic factor (BDNF) levels and pharmacokinetics of fluoxetine to determine whether they mediate sex differences. MRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 41 publications
8
59
0
Order By: Relevance
“…In contrast, there are only a few reports on the effects of FLX on neurogenesis in the SVZ [2,9,10,[15][16][17][18]. Almost all of the studies in the literature have revealed no influence of FLX on neurogenesis in the SVZ.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, there are only a few reports on the effects of FLX on neurogenesis in the SVZ [2,9,10,[15][16][17][18]. Almost all of the studies in the literature have revealed no influence of FLX on neurogenesis in the SVZ.…”
Section: Introductionmentioning
confidence: 83%
“…Almost all of the studies in the literature have revealed no influence of FLX on neurogenesis in the SVZ. In the experiments, the authors administered FLX for 2 to 4 weeks as a chronic treatment model, and the time courses that the authors used in the experiments on neurogenesis in the SVZ were the same as those in the DG [2,9,10,[15][16][17][18]. Considering that 5-HT-containing fibers and 5-HT receptor subtypes can be detected in the SVZ [19] and that a pharmacological experiment with agonists and antagonists of 5-HT receptor subtypes suggested that 5-HT regulates neurogenesis in the SVZ [19], we hypothesized that FLX has a late-onset effect on neurogenesis in the SVZ.…”
Section: Introductionmentioning
confidence: 99%
“…Also, often, treatment response is affected by sex-dependent differences in baseline behaviour, whereas the response to psychotropic drugs masks sex differences post-treatment. Importantly, sex differences in response to psychotropic drugs, are often related to pharmacokinetic sex differences and this should be taken into account when results from animal and human studies are interpreted (Nabeshima et al, 1984; Andine et al, 1999;Shelnutt et al, 1999;Hodes et al, 2010;Kokras et al, 2011a).…”
Section: Resultsmentioning
confidence: 99%
“…Also, often, treatment response is affected by sex-dependent differences in baseline behaviour, whereas the response to psychotropic drugs masks sex differences post-treatment. Importantly, sex differences in response to psychotropic drugs, are often related to pharmacokinetic sex differences and this should be taken into account when results from animal and human studies are interpreted (Nabeshima et al, 1984; Andine et al, 1999;Shelnutt et al, 1999;Hodes et al, 2010;Kokras et al, 2011a).Behavioural sex differences usually result from sex differences in neural underpinnings and/or are linked with sex differences in brain structure, neurochemistry, neuroendocrinology and neurobiology (Cahill, 2006;Cosgrove et al, 2007;Solomon and Herman, 2009). Sex differences result from chromosome effects, organizational effects of sex hormones during development of the brain and/or activational effects of sex hormones (McCarthy et al, 2012).…”
mentioning
confidence: 99%
“…During brain development, serotonin acts as a regulatory factor influencing cell proliferation, migration, and differentiation. Thus, SSRIelicited alterations in brain serotonin levels could affect these processes; hence, prenatal SSRI exposure in rats alters cell proliferation and survival in multiple areas of the fetal brain (39). Second, there could be systemic effects of transient increases in blood serotonin associated with each daily SSRI dose, resulting in repetitive bouts of reduced uterine blood flow and fetal hypoxemia, which could lead to a redistribution of fetal cardiac output as well as endocrine and metabolic changes affecting fetal growth, brain development, and gestation length (38,40).…”
Section: Discussionmentioning
confidence: 99%